Giant spin Nernst effect induced by resonant scattering at surfaces of metallic films - Long, Nguyen H.; Mavropoulos, Phivos; Zimmermann, Bernd; Blügel, Stefan; Mokrousov, Yuriy (PHYSICAL REVIEW B, 2016)
A concept realizing giant spin Nernst effect in nonmagnetic metallic films is introduced. It is based on the idea of engineering an asymmetric energy dependence of the longitudinal and transverse electrical conductivities, as well as a pronounced energy dependence of the spin Hall angle in the vicinity of the Fermi level by the resonant impurity states at the Fermi level. We employ an analytical model and demonstrate the emergence of a giant spin Nernst effect in Ag(111) films using ab initio calculations combined with the Boltzmann approach for transport properties arising from skew scattering off impurities.